Wear Analysis of AA 6082 Aluminum alloy /Fly ash Composite - Choudhury, Anup; Das, Sankar Narayan; Behera, Rabindra (International Journal of Psychosocial Rehabilitation, 2020)
Nowadays Metal matrix composites (MMCs) guides to better and attractive design. The ob- jectives are to save structural materials and utilize the waste products that are promoting in each field of engi- neering purposes. The researchers have keen attention for low density and low-cost component. Fly ash is the cheapest solid waste which is available in plenty in any of the thermal power plants. Hence, aluminum and fly ash composite found to be suitable for applications in the field of automotive and small engine applications for its low density and low cost. To fabricate Al metal matrix composites by casting technique, the Fly ash particles are add- ed into Aluminum melt about 750 degrees centigrade.The present investigation is focused on the use of sufficient- ly obtainable industrial throw away ‘fly ash’ in a beneficial approach through adding it to AA6082 aluminum metal matrix by means of fluid metallurgy route. For this purpose, following ranges of the fly ash bits ranging from 0.1µm to 100µm were used. The worn exteriors were examined using an optical microscope for varying compositions of fly-ash particles in the composites. The mechanical along with tribological properties including hardness, the abrasive wear resistance of the aluminum metal matrix was verified with the different amount of fly ash composites in the cast forms under various standardized machines and found to be improving with increasing value of fly ash content. The genuineness of improving the property is also verified as the grain size and num- bers of intercepts are found to decrease in the study of the scanning microscope.